Nanostructure and poroviscoelasticity in cell wall materials from onion, carrot and apple: Roles of pectin. (January 2020) - Lopez-Sanchez, P.; Martinez-Sanz, M.; Bonilla, M.R.; Sonni, F.; Gilbert, E.P.; Gidley, M.J.
Abstract: The hierarchical organisation of polysaccharides in primary plant cell walls is responsible for their unique mechanical properties, and in turn for the textural and rheological properties of plant-based foods and ingredients. It is expected that at the nano scale, the mechanical properties of cell wall materials arise from a combination of structural deformation of the polysaccharide networks and hydraulic properties of the continuous water phase, as has been shown for other cellulose-based composites. Pectin plays a key role in the load bearing properties of (bacterial) cellulose-pectin composites due to its contribution to both hydration structure and the dynamics of water movement. To investigate whether these features are also important in plant cell wall materials we have used a set of advanced characterisation techniques to elucidate cell wall structural features at different length scales (X-ray diffraction and small angle X-ray and neutron scattering) in cell walls from two dicotyledons (apple and carrot) and a non-commelinid monocotyledon (onion). The strength of isolated cell walls was measured under compression and fitted to a poroviscoelastic mechanical model, demonstrating that the mechanical properties of the isolated cell wall materials are directly linked to both polysaccharide networks and fluid flow through the networks. Our results show how pectin polysaccharides influence the viscoelastic behaviour of these materials and contribute to the texture of plant-derived food systems. Graphical abstract: Structural and rheological properties of cell walls from onion, carrot and tomato show how a core-shell model for cellulose fibres and a poroviscoelastic model for compressive materials behaviour are connected. Key roles for pectin are identified, depending on the level of association with cellulose microfibrils.Image 1 Highlights: Cell walls isolated from onion, carrot and apple for structure and rheology analyses. Core-shell model for cellulose fibres can be applied to SAXS and SANS data on cell walls. Poroviscoelastic model explains compressive mechanical behaviour of cell wall suspensions. Rheological parameters are consistent with cellulose and pectin amounts and interactions. Three types of pectin-cellulose interactions defined, with different mechanical consequences.